2020
DOI: 10.3390/biom10020264
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization, Nutritional and Insulin Regulation of Elovl6 in Rainbow Trout (Oncorhynchus mykiss)

Abstract: Elongation of very long-chain fatty acids protein 6 (Elovl6) is a crucial enzyme in the synthesis of endogenous fatty acids, which participates in the energy balance and metabolic diseases. The main objective of this study was to explore the molecular characterization of Elovl6 and the regulation of elovl6 expression in response to dietary fatty acids and insulin. In the present study, the ORF (open reading frame) of Elovl6 from rainbow trout was cloned and characterized, which showed a high identity (87%) wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The elovl5 was present in virtually all teleosts that were specific for the elongation of C 18 and C 20 PUFAs, and also had capacity towards C 22 PUFA in some fish, such as Pegusa lascaris 16 and Scatophagus argus 17 . The elovl6 acted to convert C 16 saturated and monounsaturated fatty acids to C 18 fatty acids, similar to mammals, which has been reported in Larimichthys crocea 18 and Oncorhynchus mykiss 19 . The novel elongase, elovl8, including elovl8a and elovl8b, were apparently absent in mammals but shown to have elongation activity to C 18 and C 20 PUFA in teleosts such as Clarias gariepinus and Siganus canaliculatus 20 .…”
supporting
confidence: 61%
“…The elovl5 was present in virtually all teleosts that were specific for the elongation of C 18 and C 20 PUFAs, and also had capacity towards C 22 PUFA in some fish, such as Pegusa lascaris 16 and Scatophagus argus 17 . The elovl6 acted to convert C 16 saturated and monounsaturated fatty acids to C 18 fatty acids, similar to mammals, which has been reported in Larimichthys crocea 18 and Oncorhynchus mykiss 19 . The novel elongase, elovl8, including elovl8a and elovl8b, were apparently absent in mammals but shown to have elongation activity to C 18 and C 20 PUFA in teleosts such as Clarias gariepinus and Siganus canaliculatus 20 .…”
supporting
confidence: 61%
“…Further, conjugated linoleic acids reduce ELOVL6 mRNA levels in lactating dairy goats (Zhang et al, 2018). In contrast, dietary α-linolenic acid or linolenic acid upregulate ELOVL6 expression in marine fish by increasing the transcriptional expression of transcription factors (i.e., CREB1, RXRα; Li et al, 2019Li et al, , 2020. In addition, a previous study showed that the inhibiting effect of PUFA on milk fat synthesis mainly through suppressing the expression of SREBF1, and then blocking the expression of related genes in milk fat synthesis (Harvatine and Bauman, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish possess two elovl1 genes, elovl1a and elovl1b, and knockdown of elovl1 increased levels of C14 to C20 SFA, MUFA and PUFA in zebrafish embryos, suggesting Elovl1 in zebrafish may also be involved in the elongation of PUFA [98], different from human ELOVL1 that has high activity toward C20 and C22 SFA and MUFA [99]. However, molecular characterization and nutritional regulation of Elovl6 was reported in loach (Misgurnus anguillicaudatus) [100], large yellow croaker (Larimichthys crocea) [101] and rainbow trout [102], with loach Elovl6 shown to elongate 16:0 and 16:1 to 18:0 and 18:1, respectively, similar to mammals [100]. While Elovl3 and Elovl7 have not yet been reported in fish, compared to mammalian Elovl7, Elovl7 from the marine crustacean orange mud crab (Scylla olivacea) had elongation activity towards 16:1n-7 and, to a lower extend, C18 PUFA [103].…”
Section: Elongation Of Very Long-chain Fatty Acids (Elovl) Proteinsmentioning
confidence: 97%